FAKTOR-FAKTOR PENYELESAIAN DAN PENYELAMATAN PINJAMAN (KREDIT MACET) DI KOPERASI ARTHA SEJATI SEMARANG - Angga Dwi Prabekti; Fitika Andraini (Fakultas Hukum Universitas Stikubank, 2018)
Lending often occurs in a loan agreement (credit), which is a State party to the debtor's inability to pay an obligation that has been mutually agreed by the lender so that losses on the part of creditors as occur at the KSP Artha True Semarang. As for the purpose of this research is to know and understand what factors being the cause of the occurrence of loans (bad credit) as well as settling the loan (bad credit) happens on the KSP Artha True Semarang. The methods used in the writing of this is empirical method that uses an approach from the aspect arising in field, which has the nature of a real legal who live in thecommunity. Formulation of the problem examined in this thesis is how writing reviews of juridical agreement loan (credit) in cooperative Artha True Semarang, what are the factors that led to the loan (kreditmacet) on Cooperative Artha True Semarang, and how the process of rescue and settlement of loans (kerdit jam) of the true Artha padaKoperasi Semarang Formulation of the problem examined in this thesis is how writing reviews of juridical agreement loan (credit) in cooperative Artha True Semarang, what are the factors that led to the loan (kreditmacet) on Cooperative Artha True Semarang, and how the process of rescue and settlement of loans (kerdit jam) of the true Artha on Cooperative Semarang From this research can generate external factors which are the cause of loan (kerdit jam) is the debtor experienced barriers/difficulties in economic needs due to an accident causing late payment in pay off in installments. While the internal factor is the weak information and oversight in causing the credit turnaround supervision be not maximum. And the efforts made in the settlement of bad debts in the KSP Artha Semarang is True through the settlement outside the Court/non litigation and settlement in court, as well as save existing assets.